Preweaning heat stress alters liver transcriptome and DNA methylation in dairy calves - Jimena Laporta; Bethany Dado-Senn; Anne R. Guadagnin; Lihe Liu; Francisco Peñagaricano (Journal of Dairy Science)
ABSTRACT: Prenatal hyperthermia has long-lasting effects on dairy calf metabolism, immunity, and productivity. Yet, the effects of postnatal heat stress on neonatal calves remain unclear. As such, this study aimed to investigate the impact of heat stress on the preweaning dairy calf liver gene expression and DNA methylation profiles. Holstein dairy calves were exposed to summer heat stress (daily average temperature-humidity index >78) for 42 d postnatally (i.e., birth to weaning) with access to active fan heat abatement (postnatal cooling, post-CL; calf-height air speed 2.05 m/s, n = 12) or not (postnatal heat stress, post-HS; calf-height air speed 0.15 m/s, n = 12). All thermoregulatory responses were lower in post-CL relative to post-HS calves throughout the experimental period (−12 bpm, −2.5°C, and −0.11°C for respiratory frequency, rectal temperature, and ear skin temperature, respectively). Liver tissue was harvested via biopsy (n = 6 male calves per treatment) at 42 d of age for RNA sequencing and reduced representation bisulfite sequencing. There were 73 differentially expressed genes (DEG), of which 31 were downregulated and 42 were upregulated in post-HS relative to post-CL treatments (false discovery rate cut-off, 20%). Ingenuity pathways analysis revealed that post-HS significantly affected 24 pathways and 60 transcription regulators, including pathway PI3K/AKT, and transcription regulators PPARGC1A, STAT5B, CREB, and XBP1. A total of 14,639 differentially methylated cytosines (DMC) were found across the entire bovine genome; these DMC mapped to 3,197 differentially methylated genes (DMG), with about 300 DMG with DMC located close to the transcription start site. These DMG, such as PKA, AMPK, MAPK, and STAT3, are closely related to metabolic signaling pathways. Overall, preweaning exposure of dairy calves to heat stress changes hepatic methylation profiles, which in turn may affect the expression of genes with critical roles in intracellular signaling and development, metabolic, and immune-related pathways. Providing mechanical cooling via fans to dairy calves in summer seems beneficial to promoting thermoregulation and liver cellular hemostasis.